Experimental model for chondrodystrophy of large bones caused by an overdose of bisphosphonates. - Mostovoy, S. O.; Ostapenko, O. V. (Морфологія / Morphologia / Morfologìâ, 2013)
The results of the influence of high doses of aminobifosfonate "Pamired" on condition of metaepifisate plates of long bones. The aim of investigation is to simulate and study the characteristics of lesions the morphostructure of organ with bisphosphonates. 48 laboratory rats at the age of 6 month were used during the investigation.The weight was about 120-150g. Femoral,humeral and tibial bones were studied with light microscopy.Degree of damage were studied with binocular microscope and photo nozzle "Canon" with enlargement 100, 800.Processes of calcification and dehydratation of cartilage caused by overdosing of remedy are shown. It lead to decrease in capacity of proliferation of chondrocytes, non-uniform width of growth plate and loss of zones.Qualitative variations at the microscopic level, which can be used as one of the models chondrodystrophy are shown.